Genetic and phenotypic parameters of milk production traits in Jamunapari goats - Prajapati, Brijesh Kumar; Singh, Kishan Pal; Mandal, Ajoy; Rout, Promad KUMAR; Roy, Ramadhar (Indian Journal of Dairy Science, 2017)
The total 2244 lactations from 835 Jamunapari does maintained (1985-2011) were analyzed 90-days, 140-days, total milk yield for this breed averaged 88.51±2.81, 132.40±4.95 and 156.01±5.06 lit., respectively. The average lactation length was 162.20±4.09 days. Significant differences among sires existed within the breed for all lactation traits. There were period of kidding had highly significant (P<0.01) effect on all lactation traits. Significant (P<0.01) differences in milk yields as well as lactation length exist among does of different parities (ages). Higher milk yields were observed in 6 or more parities does as compared to does of younger parities. Season of kidding had significant (P<0.01) influence on all lactation traits except lactation length. Non-significant effect of type of birth on all lactation traits of Jamunapari goats. The interaction effect between period of kidding and season of kidding was also significant (P<0.01) for all lactation traits. and heritabilities of all lactation traits were moderate in magnitude, ranging from 0.88 to 0.99. Similarly, the genetic and phenotypic correlations of MY140D with TMY were also high (rp = 0.93, rg= 0.97) and significant. The phenotypic and genetic correlations of LL with MY90D, MY140D and TMY ranged from medium to moderately high (0.22 to 0.55) in this study.